2007
DOI: 10.1086/523873
|View full text |Cite
|
Sign up to set email alerts
|

Stringent Criteria for Stable and Unstable Planetary Orbits in Stellar Binary Systems

Abstract: The existence of planets in stellar binary (and higher order) systems has now been confirmed by many observations. The stability of planetary orbits in these systems has been extensively studied, but no precise stability criteria have so far been introduced. Therefore, there is an urgent need for developing stringent mathematical criteria that allow us to precisely determine whether a planetary orbit in a binary system is stable or unstable. In this Letter, such criteria are defined using the concept of Jacobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
8
30
0
Order By: Relevance
“…Comparisons to previously established criteria for stability show that our results are consistent with previously obtained stability limits (e.g., Holman & Wiegert 1999;Musielak et al 2005;Cuntz et al 2007;Eberle et al 2008;Eberle & Cuntz 2010). In Eberle et al (2008), Paper I, the onset of instability was related to the topology of the ZVC, whereas in Eberle & Cuntz (2010), Paper II, it was shown that the onset of orbital instability occurs when the median of the effective eccentricity distribution exceeds unity.…”
Section: Discussionsupporting
confidence: 91%
“…Comparisons to previously established criteria for stability show that our results are consistent with previously obtained stability limits (e.g., Holman & Wiegert 1999;Musielak et al 2005;Cuntz et al 2007;Eberle et al 2008;Eberle & Cuntz 2010). In Eberle et al (2008), Paper I, the onset of instability was related to the topology of the ZVC, whereas in Eberle & Cuntz (2010), Paper II, it was shown that the onset of orbital instability occurs when the median of the effective eccentricity distribution exceeds unity.…”
Section: Discussionsupporting
confidence: 91%
“…A comparison with the zero-velocity contour of the planetary orbit shows that this criterion, which is a sufficient criterion for orbital instability, closely coincides with the opening of the zero-velocity contour at the Lagrange point L3, located to the right of the primary star, as discussed by Cuntz et al (2007) and Eberle et al (2008). If instability occurs, extremely large effective eccentricities are found, indicating a highly hyperbolic planetary orbit in the synodic coordinate system, a stark indication of planetary escape.…”
Section: Discussionsupporting
confidence: 62%
“…Previous results have been obtained by, e.g., Musielak et al (2005), Cuntz et al (2007), and Eberle et al (2008). In the following, we present a new method that relies on a differential geometrical approach based on the analysis of the curvature of the hodograph in the synodic coordinate system.…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…In the case of the CR3BP, the stability limits previously obtained have recently been updated by Cuntz et al (2007) and (Eberle et al 2008, Paper I) based on an analytical approach. Cuntz et al and Eberle et al were able to derive a stringent (sufficient) criterion for orbital stability based on Jacobi's constant and Jacobi's integral, akin to the criterion of "Hill stability".…”
Section: Introductionmentioning
confidence: 99%